2017
DOI: 10.1590/1806-9061-2016-0447
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Synthetic Antioxidant Treatment in Stabilizing Poultry Byproduct Meal and Subsequent Impact of the Treated Meal on Selected Growth Parameters of Broilers

Abstract: This study was conducted to investigate the effect of a commercial antioxidant (CAO; Rendox Plus ® ) treatment in stabilizing the poultry byproduct meal (PBPM) and then the subsequent effect of the treated PBPM on growth of broilers. Five batches A, B, C, D and E of PBPM were treated with CAO at 0, 250, 500, 750 and 1000 mL/ton, respectively and stored for 42 days. Oxidative stability of PBPM was estimated on day 0 and then weekly using Peroxide Value and Thiobarbituric Acid tests. PBPMs treated with 750 &1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(23 reference statements)
0
3
1
Order By: Relevance
“…(Figure 2) indicated that the control sample (T1), with no antioxidant inclusion had lower rancidity than samples treated with ginger as a natural antioxidant at day 1. The observed result is this study does not support report by Ahmad, et al, (2017) who reported significant decrease in POV of PBPM with increase in antioxidant application. This could be due to the method of processing employed in this study and/or the application of synthetic antioxidant which offered immediate free radicals to control/ reduces the rancidity from the first d a y .…”
Section: Evaluation Of Poultry By-product Meal Treated With Ginger (Zcontrasting
confidence: 99%
“…(Figure 2) indicated that the control sample (T1), with no antioxidant inclusion had lower rancidity than samples treated with ginger as a natural antioxidant at day 1. The observed result is this study does not support report by Ahmad, et al, (2017) who reported significant decrease in POV of PBPM with increase in antioxidant application. This could be due to the method of processing employed in this study and/or the application of synthetic antioxidant which offered immediate free radicals to control/ reduces the rancidity from the first d a y .…”
Section: Evaluation Of Poultry By-product Meal Treated With Ginger (Zcontrasting
confidence: 99%
“…Energy-rich ingredients are expensive in broiler diets [ 1 , 2 ]. Maximizing the retention of energy for growth by applying a non-nutritive factor should therefore be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Most popular applications used to enhance meat quality and stability (Avila-Ramos et al, 2013) are usually done by dietary commercial additives (Wood and Enser, 1997;De Zawadzki et al, 2017). These additives also enhance the growth and health status of animals, prevent dietary oxidation, and raise their immunity (Gopi et al, 2014;Ahmad et al, 2017). Several antibiotics and synthetic additives (e.g.…”
Section: Introductionmentioning
confidence: 99%